Navigating a Conflictual Past for a Reconciled Future: Memory Politics and Democracy in Indonesia - Sarah Davidson (Jurist-Diction, 2026)
More than five decades after the 1965–66 mass violence, Indonesia continues to grapple with the legacy of an unresolved past. This article examines how state-sponsored memory politics surrounding the genocide has shaped Indonesia’s democratic trajectory and hindered efforts toward reconciliation. Drawing on theories of collective memory, memory abuse, sites of memory, and the state of exception, the study employs a normative and qualitative analysis of historical narratives, legal developments, public policies, and memory activism in post-authoritarian Indonesia. The findings demonstrate that the New Order regime institutionalized a dominant historical narrative through education, propaganda, censorship, and memorialization practices that legitimized state violence and marginalized victims’ experiences. Although democratic reforms after 1998 created greater space for public discussion, impunity, historical distortion, and militarized governance continue to persist. At the same time, civil society actors, survivors, artists, and digital activists have developed alternative forms of memory-making that challenge official narratives and promote historical accountability. The article argues that meaningful democratic consolidation requires confronting the legacy of 1965 through truth-seeking, educational reform, inclusive memorialization, and participatory mechanisms of reconciliation. Without addressing this conflictual past, Indonesia’s democratic future will remain fundamentally incomplete.